Dynamic Economic Dispatch On Micro Grid Electrical Systems Using Quadratic Programming - Heri Suryoatmojo; Fakhruddin Wirakusuma; Rony Seto Wibowo (Department of Electrical Engineering ITS and FORTEI, 2018)
Currently the needs of electric power increased rapidly along with the development of technology. The increase in power requirements is contrary to the availability of sources of energy depletion of oil and coal. This problem affects the national electrical resistance. To meet the needs of large electric power with wide area coverage is required small scale distributed power generation. This distributed generation (DG) of renewable energy sources sought to minimize the use of energy resources such as oil and coal and connected to the micro grid and use the battery as a power balance. Because of there are many DGs and the use of batteries, therefore it is important to determine the optimal power generation of each plant as well as the use of battery based on the optimal capacity so that requirement of electric power can be met with minimal cost each time. This optimization is known as Dynamic Economic Dispatch. In this study, the methods of Quadratic Programming is required to solve the optimization problem.Keywords: micro grid, Dynamic Economic Dispatch, Quadratic Programming, Battery, Energy Storage